Uses of Logistic and Generalized Linear Models to Describe the Social Outbreak in Colombia. What discussions are promoted in university students? (Encuentros, 2024)
This article analyzes the use of mathematical models in statistics and mathematics undergraduate students at the Universidad del Valle to generate mathematical, technological and reflective discussions, when studying a model that describes some factors present in the social outburst occurred during 2021 in Colombia. Through qualitative methodology and case study, interviews conducted using Critical Mathematics Education and the socio-critical perspective of modeling were examined. The study of these factors was supported by the use of programming languages such as Python, Rstudio, Wolfram Alpha together with tools such as integral and differential calculus and differential equations. The results obtained show the different approaches to mathematical, technological and reflective discussions, which are related to the competences acquired during professional training; for each case, the particularities, applications, interpretations, evaluations and uses of mathematical models are detailed.
Keywords: Modeling; University Education; Logistics Function; Programming; Math; Regressions; critical mathematics education